Odpowiedzi

2010-01-08T15:27:27+01:00
Xy-2x+3y-6=6
xy-2x+3y=12

y=3.5
x=1

licze na naj odp;)
1 5 1
Najlepsza Odpowiedź!
2010-01-08T20:01:06+01:00
Xy-2x+3y-6 =6
(x+3)(y-2)=6
są one całkowite więc
x+3=6 i y-2=1 czyli x=3,y=3
lub
x+3=1 i y-2=6 czyli x=-2,y=8
lub
x+3=-1 i y-2=-6 czyli x=-4,y=-4
lub
x+3=-6 i y-2=-1 czyli x=-9,y=1
lub
x+3=2 i y-2=3 czyli x=-1,y=5
lub
x+3=3 i y-2=2 czyli x=0, y=4
lub
x+3=-2 i y-2=-3 czyli x=-5,y=-1
lub
x+3=-3 i y-2=-2 czyli x=-6,y=0
ostatecznie
rozwiązaniem są pary liczb (x,y)∈{(3,3),(6,8),(-6,-4),(-9,1),(-1,5),(0,4),(-3,-1),(-2,0)}
1 5 1